ASIMETRI INFORMASI DAN TEORI KEAGENAN PADA PENGUNGKAPAN LAPORAN KEUANGAN - Adellya Nihayatul Muuna; Elvy Prastikawati; Anna Nur Laili; Muna Widya Sari; Ardyan Firdausi Mustoffa (ITB AAS INDONESIA, 2023)
This research aims to find factors that can minimize information asymmetry due to agency relationships through disclosure of financial statements. The method of this research is a review article with library sources from online media with the theme of financial statement disclosure, information asymmetry theory, and agency theory. The results show that information asymmetry occurs because of the agency relationship within the company. This information asymmetry can be minimized by disclosing financial reports through factors such as Other Comprehensive Income Disclosures, Enterprise Risk Management Disclosures, and Disclosure Quality. Keywords : Asimetri information, Agency Theory, Financial Statement Disclosure